Custos relacionados a anticoagulação oral em pacientes com fibrilação atrial não valvar - Guerrero, Andressa Zulmira Avila [UNIFESP] (2021)
Background: atrial fibrillation is a public health problem with a fivefold increased risk of stroke or death. Analyzing costs is important when introducing new therapies and must be recalculated in special situations, such as the novel coronavirus pandemic of 2020. Objective: This study aimed to evaluate the costs and quality of life related to anticoagulant therapy of atrial fibrillation during 1 year, in patients treated in a public university hospital. Methods: Patient costs were those related to the anticoagulation and calculated by the average monthly costs of warfarin or direct oral anticoagulants. Patient non-medical costs (eg., food and transportation) were calculated from data obtained by questionnaires. The Brazilian SF-6D was used to measure the quality of life.P-values< 0.05 were considered statistically significant. Results: The study population consisted of 90 patients, 45 in each arm (warfarin vs direct oral anticoagulants). Costs were 20% higher in the direct oral anticoagulants group ($55,532.62 vs $46,385.88), most being related to drug price ($23,497.16 vs $1,903.27). Hospital costs were higher in the warfarin group ($31,088.41 vs $24,604.74) and related to outpatient visits. Additionally, nonmedical costs were almost 2 times higher in the warfarin group ($13,394.20 vs $7,430.72). Costs equivalence can be reached with 0.61x/DOACs drug prices. There were no significant group differences in the quality of life. Conclusions: Direct oral anticoagulants group costs were higher than warfarin group. However, reducing 40% of the drug price may be feasible to incorporate direct oral anticoagulants into the Brazilian public health system.